Academic Faculties Job satisfaction in Tribhuvan University: A Case study of Padmakanya Multiple Campus (Voice of Teacher, 2024)
Job satisfaction is the study of employees’ attitude and behavior at work. The objective of this study was to analyze the job satisfaction level in Academic Faculties of Padmakanya Multiple Campus. For that purpose, 97 Academic Faculties were selected under purposive random sampling method from Humanities and Social Science, Management Faculty and Institute of Science and Technology. The structured questionnaires were designed under the guideline of Job description index at five points Likert Scale. Only 78 respondents' opinion were analyzed on the helps of mean, standard deviation and ANOVA analysis. The analysis has shown job satisfaction level of maximum Academic Faculties more than 3.5 mean value of committed at work, job securities, job itself, responsibilities, coworkers, responsibility, supervisor, personal growth. The Academic Faculties have not beliefs campus administration and policies maker’s interest on welfare and overall satisfaction of employees. The demographical factor age groups have different impact on job satisfaction of Academic Faculties in the Campus. But the job satisfaction of Academic Faculties of the Campus has not shown significantly differences in job satisfaction according to work experience. The Campus Management and policy makers should enhance the job satisfaction level of Academic Faculties in Campus by participating in decision-making process such as time base Campus General Assembly, call suggestions to enhance academic performance, physical infrastructure development, financial benefits etc. They feel respect, recognition, interaction with co-worker, maintain relation with campus chiefs, assistance campus chiefs etc. boost up job satisfaction in Academic Faculties etc.